A brief comment on the dynamical behavior of a forced nonlinear slewing beam: 1. Superharmonic resonance - Fenili, A.; Souza, L. C. Gadelha De; Balthazar, J. M. [UNESP]; Góes, L. C. S. (Associação Brasileira de Engenharia e Ciências Mecânicas - ABCM, 2005)
This paper describes the dynamical behavior of a nonlinear flexible beam (cubic nonlinearities considered) connected to a dc motor (responsible for the slewing motion) when the angular displacement of the slewing axis and its derivatives are considered to be of a harmonic type and the system is excited near a resonance (present due to the nonlinear contribution).
Keywords: Slewing structure; nonlinear vibrations; resonance; multiple scale method